Determinants of FDI: Evidence from Developed & Developing Countries - Ibrahim, Tarek (AUC Knowledge Fountain, 2019)
This study investigates the generic determinants of foreign direct investment (FDI) assessed using data for 65 countries over the period between 1991 and 2017 by employing a panel data model. The goal of this study is to provide a more holistic view that highlights the variables that are significant in determining FDI regardless of the widely varying economic and institutional platforms across countries, regions and continents. The countries selected vary widely across trade facilitating infrastructure, technology platform, investor perception/ investment profile and economic environment. This study also applies control variables GDP, GDP per Capita, population, and inflation to avoid omitted variable bias. Results show that the generic variables that drive FDI are Exports as percentage of GDP, Imports as a percentage of GDP, Gross Fixed Capital Formation as a percentage of GDP, General Government Final Expenditure as a percentage of GDP, Cellular Subscription as a portion of population and International Country Risk Guide Investment Profile. On the other hand natural resource rents, tax revenue as a % of GDP, and GDP growth do not result to be significant in FDI for this wide-ranging dataset. Research Contribution: This study contributes to the topic in that: o It criticises Ease of Doing Business Indicators due to methodological inconsistencies and mechanical changes of index computation and replaces these variables with International Country Risk Guide Indices that measure institutional quality in addition to Freedom House Civil Liberties and Political Rights. o Unlike most recent literature, seeks to determine a large categorically diverse group of variables over a large set of characteristically diverse countries, in determining the variability of FDI. In addition, although there is abundant research of this topic, new research and new assessment techniques continue to surface on the topic due to FDI importance and potential in shifting the fortunes of global economies and standards of living. The limitation of this study is that policy makers may need to complement this research with existing abundant FDI determinants research, narrower in scope and detail oriented in terms of dimension; i.e. countries, regions, and variables. Accordingly, governments may have a more comprehensive view based on recent research in determining FDI seeking based policy.